New results on light nuclei, hyperons and hypernuclei from HADES (HADES collaboration) - Abou Yassine Rayane; Adamczewski-Musch Jörn; Becker Marten; Bergmann Philip; Blanco Alberto; Blume Christoph; Chlad Lukas; Chudoba Petr; Ciepał Izabela; Cordts Malte; Dreyer Jörn; Esmail Waleed Ahmed; et al. (EPJ Web of Conferences, 2022)
In March 2019 the HADES experiment recorded 14 billion Ag+Ag collisions at √sNN = 2.55 GeV as a part of the FAIR phase-0 physics program. In this contribution, we present and investigate our capabilities to reconstruct and analyze weakly decaying strange hadrons and hypernuclei emerging from these collisions. The focus is put on measuring the mean lifetimes of these particles.